An analysis of harms reporting in systematic reviews regarding ketorolac for management of perioperative pain. (November 2022) - Modi, Jay; Magee, Trevor; Rucker, Brayden; Flores, Holly; Wise, Audrey; Kee, Micah; Garrett, Morgan; Roberts, Will; Vassar, Matt
Abstract: Background: Owing to the frequent perioperative use of ketorolac tromethamine and its ability to minimise postoperative opioid requirements, it is important to continually reassess harms associated with its use. Our primary objective was to investigate the extent of harms reporting in systematic reviews (SRs) on ketorolac for perioperative pain. Methods: In May 2022, we conducted a search of major databases, MEDLINE (PubMed and Ovid), Embase, Epistemonikos, and the Cochrane Database of Systematic Reviews to identify eligible SRs on ketorolac for perioperative pain. Screening and data extraction were performed in masked, duplicate fashion. A MeaSurement Tool to Assess systematic Reviews-2 (AMSTAR-2) was used to appraise the methodological quality of included SRs. Corrected covered area (CCA) was calculated to determine overlap of primary studies between SR dyads. Results: A total of 28 SRs evaluating 630 primary studies met the inclusion criteria. Seven SRs (7/28, 25%) reported no harms and 17 SRs (17/28, 60.7%) reported ≤50% of harms items. A significant association was found between completeness of harms reporting and whether harms were specified as a primary outcome ( P <0.001). No other associations were statistically significant. Regarding methodological quality, 22 SRs were appraised as 'critically low' (22/28, 78.6%), 5 as 'low' (5/28, 17.9%), and 1 as 'high' (1/28, 3.6%). One SR dyad had a CCA >50% but neither reported harms. Conclusions: The extent of harms reporting in systematic reviews was inadequate. Given the importance that systematic reviews have on guiding perioperative decision-making, it is essential to improve the completeness of harms reporting.